Association Between Patient and Emergency Department Operational Characteristics and Patient Satisfaction Scores in a Pediatric Population. Issue 3 (March 2016) - Nichol, Jonathan Robert; Fu, Rongwei; French, Keith; Momberger, Jami; Handel, Daniel A.
Abstract : Background: Emergency departments (EDs) are seeing an increase in the importance of patient satisfaction scores, yet little is known about their association with patient and operational characteristics. Objectives: This study aimed to identify patient and operational characteristics associated with patient satisfaction scores. Methods: This was a retrospective analysis of data from Press Ganey patient satisfaction surveys of pediatric patients (<18 years) and their families, discharged from the ED of a single, academic, pediatric ED from December 2009 to May 2013. A linear mixed-effects regression model was used to identify significant associations while taking the clustering within patients and physicians into account. Outcome variables included scores for overall experience (0–10), wait time to be seen by a provider (0–100), and likelihood to recommend (0–100). The ED characteristics considered included daily census, proportion of left without being seen, average length of stay (LOS), and total boarding hours, as well as time of day by shift, door-to-room time, and discharge LOS. Patient characteristics included pa tient age, sex, race, person completing survey, survey language, survey method (mailed or online), payer type, mode of arrival, distance to hospital, weekend or weekday visit, and difference of patient-reported LOS to actual LOS. Only statistically significant variables were included in the final model. Results: A total of 810 pediatric surveys were included for analysis. The overall mean (SD) was 8.7 (2.0) for overall experience, 84.0 (23.5) for waiting time to be seen by a provider, and 90.1 (22.2) for likelihood to recommend. The score for overall experience was highly correlated with likelihood to recommend (r = 0.90) and less strongly correlated with score for waiting time (r = 0.58). In the final models, increased door-to-room time was associated with a significant decrease in scores for all 3 outcome variables. In addition, a difference between perceived and actual LOS (>2 hours) was significantly associated with lower scores in overall experience and likelihood to recommend, whereas surveys completed online had higher scores for waiting time to see a provider compared with mailed. Conclusions: Emergency departments looking to increase satisfaction scores should focus efforts on decreasing door-to-room times.